(untitled) (Brazilian Journal of Oceanography, 2008)
Natural assemblages show large variability at multiple scales in space and time as a consequence of several abiotic and biotic factors. This study was conducted in the surf zone of Arraial do Cabo (22º 58'S, 42º 01'W) and tested the hypothesis that the ichthyofauna composition and structure differ according to the tidal variation at three beaches with different morphodynamic characteristics. From September 2001 to August 2002 three monthly hauls were carried out at each beach during high (N = 6) and low tide (N = 6) with a beach seine (25 m length, 2,50 m height, 10 mm mesh). At Praia Grande and Prainha beaches, the number of species and individuals was higher during low tide. Also, CPUE (grams) at Praia Grande and Prainha was higher during high tide indicating a movement of many benthivore and piscivore species into the intertidal zone, due to the greater food availability. The fish community structure differed between Prainha and Praia Grande according to the tide in relation to fish biomass, which was higher at high tide, except for Praia dos Anjos (low tide) partially supporting the initial hypotheses. However, the number of individuals and species richness and diversity were higher during low tide, different from the proposed statement, as a reflex of juvenile individuals' abundance.